Effect of using Fibre on the Durability of Asphalt Pavement - Akbari Motlagh, Ali; Mirzaei, Ebrahim (Salehan Institute of Higher Education, 2016)
Using the fibre additives with a uniform distribution in asphaltic concrete mixture is a well-known technique for improving the mechanical properties and durability of asphalt pavement. The purpose of this study is to investigate the effect of preparing fibre and production of the properties of bitumen and asphalt concrete mixture. In this study, a dense-graded aggregation, mineral fibres (asbestos) and synthetic fibres (polyester and nylon) were used.Â Laboratory studies were done by comparing different rheological properties, mechanical and moisture susceptibility of mixtures of fibres. Results of the penetration and softening point on mixtures of bitumen â€“ fibre show that fibres improve the mixed rheological properties and stiffening effect of fibre properties. The results of Marshall Tests indicate that adding fibres reduces the strength in Marshall and results in the slight increase in the percentage of optimum bitumen content and asphalt percentage of air voids in comparison with typical fibre. The results of the indirect tensile tests showed that the addition of fibres, depending on the percentage of fibres significantly improves the durability of the mixture.